Forest-based bioenergy policies in five European countries: An explorative study of interactions with national and EU policies. (September 2015) - Lindstad, B.H.; Pistorius, T.; Ferranti, F.; Dominguez, G.; Gorriz-Mifsud, E.; Kurttila, M.; Leban, V.; Navarro, P.; Peters, D.M.; Pezdevsek Malovrh, S.; Prokofieva, I.; Schuck, A.; et al.
Abstract: In this explorative study, we compare national policies affecting production and use of forest-based bioenergy in five European countries: Finland, Germany, Norway, Slovenia and Spain. Our methodological approach combines horizontal and vertical policy interaction with three policy layers: policy objectives, policy instruments and thematic elements in implementation. Great variations are found in national bioenergy policies, with complex interlinkages revealed to national renewable energy and forest policies (horizontal dimension) and to EU policies (vertical dimension). Horizontally, the national bioenergy objectives are closely linked to forest policy objectives and, in Finland, also to renewable energy objectives. Policy instruments promoting bioenergy demand interact to various degrees with both renewable energy and forest policies, while supply side instruments, as well as implementation aspects, interact most closely with forest policies. Vertically, highest degree of interactions with EU polices are in this study revealed for policy objectives and instruments, less so for implementation. It is concluded that consideration of policy layers are useful for increasing the understanding of the complexity in horizontal and vertical policy interactions, and thus an important basis for understanding how to minimize conflicts and enhancing synergies among multiple forest objectives. We argue that the chosen analytical framework can enhance the understanding of complex interlinkages between bioenergy and broader policy and market developments. Identifying these complex interactions can contribute to facilitate policy developments promoting and regulating future production and use of forest-based bioenergy, while taking other forest objectives into consideration. Highlights: Horizontal and vertical policy interactions vary greatly across policy layers. Bioenergy policies interact with national forest and renewable energy policies. National bioenergy policies are influenced by EU climate and energy policies. Policy layers help illuminate complexity in policy interactions. Analytical framework can serve structured analysis of policy interactions.